Desenvolvimento de aditivo plastificante e retardador de pega para gesso a partir da mucilagem da palma forrageira - Monteiro, Aline Gomes de Sousa (2015)
The use of gypsum in the building industry has been growing since 1990. The current plaster coating quick and easy application and is being widely used in construction due to its low cost. However, implementation of this coating generates a huge amount of waste, since it has high speed hardening and have not yet developed economically feasible technologies or applications that allow its reuse. To reduce the waste generated by the production of gypsum, adding a fire retardant additive that provides increased setting time is needed, offering longer workability of the product. This study aims to develop an additive retardant plasticizer for gypsum blocks from the mucilage of Opuntia Ficus Indica forage Palma and the evaluation of their performance through laboratory tests. The following steps were followed: Processed palm mucilage extraction, specific additive mass testing and determination of pH, application in gypsum slurry for setting time tests, absorption, compression and consistency. Based on the results it can be concluded that the additive to be used as fire retardant and plasticizer values obtained satisfactory for use. The setting time of the evaluation confirmed their retarding action on the handle start and end time grip. In compression analysis, the smaller the percentage of the additive used, greater strength. The absorption test showed that the specimen was more moisture containing the A(wather) / G(Gipsum) ratio largest and the smallest value corresponds to the smallest amount of water with the addition of the additive. As for the consistency test, the pulp with the addition of the additive possessed satisfactory values compared to reference values.